Hukum dan Kearifan Lokal Dalam Penyelesaian Perselisihan Hubungan Industrial - Ashadi l. Diab; Iskandar Iskandar (TASAMUH: Jurnal Studi Islam, 2021)
This study discusses how is the implementation of industrial relations resolution through the industrial relations court in the Kendari District Court? Is the local wisdom-based approach capable of providing legal certainty to both parties? To what extent is the District Court's efforts to resolve disputes through a local wisdom approach?In this study, the author uses the theory of legal change and the legal system and the theory of conflict. The results of the study indicate that the settlement of industrial relations disputes is a difference of opinion which results in conflicts between employers or a combination of employers and workers / laborers. In order to resolve industrial relations disputes, it can be done in two ways. First, through the pathway outside the industrial relations court, which includes mediation, conciliation, bipatrite and arbitration based on local wisdom. The second is through the industrial relations court. The local wisdom-based approach is very able to provide legal certainty through out-of-court channels, but the place to process through local wisdom is not yet adequate or there is no proper Regional Regulation that regulates it, especially in Kendari, Southeast Sulawesi. So that if there is a Regional Regulation, it is easier for the Department of Labor to process based on the applicable rules that are compounds with local wisdom. The efforts of the District Court in resolving disputes through a local wisdom approach. A number of facts show that cases handled by legal institutions before the birth of Law No. 13 of 2003 and Law No. 2 of 2004, not fully resolved. With the birth of the two laws mentioned above, most of the shortcomings as previously happened can be overcome